Charade [videorecording (DVD)] - Mancini, Henry (Universal Studios Home Entertainment, 2012)
Regina finds herself pursued through the streets of Paris by several men in search of the fortune that her murdered husband stole from them. As her world becomes entangled with suspense, murder and plots twists, she finds herself leaning on a suave, charming stranger whose motives are unclear.